Language Use in Cancel Culture Practices on X: A Critical Discourse Analysis - Rizky Afifah, Dea; Ni Made Diana Erfiani; Yohanes Octovianus L. Awololon; Putu Chrisma Dewi (Jurnal Pendidikan dan Sastra Inggris, 2026)
The widespread use of social media has given rise to cancel culture, a collective practice of publicly condemning or withdrawing support from individuals deemed to have violated social norms. While this phenomenon has grown increasingly prominent on platforms like X (formerly Twitter), the linguistic strategies underlying cancel culture discourse remain underexplored. This study aims to analyze language use in cancel culture practices on X using Fairclough's Critical Discourse Analysis (CDA) framework, covering three analytical dimensions: text, discursive practice, and sociocultural practice. Data were collected through non-participant observation of publicly available posts on X, with 27 tweets selected using purposive sampling and 12 representative tweets analyzed in depth. The findings reveal four discursive positions within cancel culture discourse: pro-cancel, anti-cancel, negotiated, and personal impact. At the textual level, users employ evaluative, imperative, and emotionally charged language to construct moral judgments and mobilize collective action. At the discursive practice level, intertextuality and polyphony characterize how cancel culture spreads across multiple digital conversations simultaneously. At the sociocultural level, the discourse reflects broader ideological tensions around gender, class, and accountability, showing that cancel culture operates differently depending on the social and cultural context in which it occurs. These findings suggest that language in cancel culture actively reproduces power relations and social norms in digital spaces.